Risky Treatments: A Jewish Medical Ethics Perspective - Steinberg, Avraham (Rambam Maimonides Med J, 2015)
The Jewish principle concerning a decision with regard to a dangerous treatment is as following: A patient who is estimated to die within 12 months because of a fatal illness is permitted to undergo a treatment that on the one hand may extend his life beyond 12 months, but on the other hand may hasten his death. There are, however, several limitations to this ruling related to the chances of success with the proposed treatment, the nature of the treatment, whether it is intended to be curative or merely to postpone the danger and death, whether the treatment is absolutely necessary, and others. One is not obligated to undergo a dangerous treatment, but one is permitted to do so. The permissibility to forfeit a short life expectancy in order to achieve more prolonged life applies only with the patient’s consent. That consent is valid and is not considered a form of attempted suicide. Neither is a refusal to submit to treatment considered an act of suicide; the patient has the right to refuse a dangerous procedure. In all situations where a permissive ruling is granted for a patient to endanger his short life expectancy, the ruling should be arrived at after careful reflection and with the approval of the rabbinic authorities acting on the recommendation of the most expert physicians.